Evaluasi Potensi Antikanker Senyawa Daun Kelor melalui Kimia Medisinal - Amin, Saeful; Pujiyani, Delya; Rusiyana, Nisrina Putri; Azzahra, Shafa Meyliana (Penerbit Goodwood, 2025)
Purpose: This study aimed to assess the potential of bioactive compounds found in moringa (Moringa oleifera) leaves as agents to treat breast cancer using a medicinal chemistry approach. Methodology/approach: This study was conducted using a descriptive and qualitative literature review approach, utilizing data sources from various relevant scientific journals published in the last five years. Results/findings: This study showed that four key compounds, moringin, kaempferol, quercetin, and nanoquercetin, have significant biological potential in inhibiting the growth and spread of breast cancer cells through various molecular mechanisms. The combination of these compounds provides a synergistic and selective therapeutic approach and shows potential in the development of more effective cancer therapies with minimal side effects. However, challenges related to pharmacokinetic limitations, especially in quercetin, can be overcome through technological innovations, such as nano-based delivery systems. Conclusions: This study concludes that bioactive compounds in Moringa oleifera leaves possess promising anticancer properties against breast cancer through diverse molecular mechanisms. Their synergistic potential highlights the relevance of natural compounds in the development of selective and effective cancer therapies. Limitations: The study was limited by its reliance on secondary data from literature sources and lack of experimental validation. Additionally, pharmacokinetic challenges, especially for quercetin, necessitate further research on delivery system optimization. Contributions: This research adds valuable insights into the medicinal chemistry of natural compounds, particularly in the Indonesian context. It also encourages the development of innovative drug delivery technologies to enhance the clinical applications of plant-derived anticancer agents.